Clinical outcomes after increasing bladder outlet resistance without augmentation cystoplasty in neurogenic bladder. Issue 2 (April 2021) - Weaver, J.K.; Coplen, D.E.; Knight, B.A.; Koenig, J.S.; Vricella, G.J.; Vetter, J.; Traxel, E.J.; Austin, P.F.
Summary: Introduction: Patients with neurogenic bladder (NGB) and urinary incontinence (UI) due to low bladder outlet resistance may require bladder neck procedures (BNPs) to achieve continence. These patients may also have reduced bladder capacity and or elevated detrusor storage pressures that require augmentation cystoplasty (AC). AC is not without complications that include risks for bladder rupture, urolithiasis, urinary tract infections and metabolic issues. Avoidance of AC would be helpful in patients with neurogenic urinary incontinence that have safe bladder parameters in the setting of low bladder outlet resistance. Objective: To determine if pre-operative urodynamics could select children with NGBs and UI for isolated BNPs without AC. Additionally we sought to determine the safety of BNPs without AC and future need of AC with long-term follow-up. Study design: This is an IRB-approved retrospective analysis of all patients undergoing BNPs for management of neurogenic UI over a 17-year period. We separated these BNP patients into two groups: No AC + BNP (Group 1) vs. AC + BNP (Group 2). Our primary analyses focused on postoperative outcomes for patients in Group 1. Outcomes assessed included additional surgical procedures, urodynamic changes, development of CKD, new hydronephrosis (HDN) and vesicoureteral reflux (VUR). Secondary analysis included the timeline for the development of any bladder deterioration that necessitated AC in Group 1. Results: 93 patients underwent BNP at a mean age of 10.8 years. Thirty did not have AC at the time of surgery (Group 1). These children had larger (p < 0.001) and more compliant (p < 0.001) bladders than Group 2 having simultaneous augmentation. At 6 years mean follow-up in Group 1 patients, three developed new reflux and three had new hydronephrosis. Nine (30%) had additional continence procedures. Twelve required (40%) AC at a mean of 23 months after the initial BNP. No patients had AC after 5 years. Detrusor end filling pressure increased 14.8 cm H2O (p = 0.028) and expected bladder capacity decreased 26.1% (p = 0.005) after isolated BNP. Discussion: We found that from our cohort of patients who had normal bladder compliance and normal/near normal expected capacity preoperatively 40% required subsequent AC. We were unable to find pre-operative clinical parameters which predicted failure or conversion to AC. We found that 43.3% of our BNP without AC patients had no subsequent invasive procedures with mean 6-year follow-up. We found that none of our patients developed any degree of CKD. Finally, we found that the majority of patients that converted to AC after their BNP did so within the first 2 years after their initial BNP and no patients required augmentation 5 years post their initial BNP. This data validates that these patients require very strict follow up, particularly in the first 5 years after surgery. Conclusions: BNP without AC is safe in only a few selected patients with NGB. Despite preoperative selection, there are significant changes in bladder dynamics and 40% required subsequent augmentation. Bladder deterioration occurs early and generally in the first 2 years. Since there are no apparent reliable pre-operative variables predicting the need for subsequent AC, parents should be counseled regarding vigilant post-operative follow-up. Summary Fig. Augmentation free following their initial bladder neck procedure. Summary Figure